TRANSFORMATION OF PESANTREN ORGANIZATIONAL CULTURE: STRATEGIES FOR PESANTREN TO BECOME CENTERS OF INNOVATION IN THE DIGITAL ERA - Risqi setiorini; Siti Aimah; Fatiyah Mohd. Fakhruddin (STAI Ma'had Aly Al-Hikam Malang, 2024)
This study examines the transformation of organizational culture in pesantren (Islamic boarding schools) in response to the challenges and opportunities of the digital era. It explores how pesantren can become centers of innovation while preserving traditional values. Using a qualitative case study approach, the research gathered data through interviews, observations, and documentation from pesantren leaders, administrators, teaching staff, and students. The data were analyzed using an interactive model, including data reduction, presentation, and conclusion drawing. The findings reveal that visionary and inclusive leadership plays a crucial role in driving innovation within pesantren, despite facing internal resistance to change. Pesantren that manage the process of change effectively demonstrate the potential to become hubs of innovation by integrating digital technology with traditional Islamic education. These pesantren preserve their core values while adopting new tools and approaches to enhance learning and administration. The study concludes that pesantren can thrive in the digital era by strategically managing cultural transformation, fostering innovation, and staying true to their educational mission. The results suggest that pesantren leaders must prioritize flexibility, collaboration, and adaptability to create an environment conducive to innovation and digital transformation. Keywords: Organizational Culture Transformation; Innovation Strategy; Pesantren; Digital Era. Abstrak Penelitian ini mengkaji transformasi budaya organisasi di pesantren sebagai jawaban terhadap tantangan dan peluang di era digital. Guna mengeksplorasi bagaimana pesantren dapat menjadi pusat inovasi dengan tetap melestarikan nilai-nilai tradisional. Dengan menggunakan pendekatan studi kasus kualitatif, penelitian ini mengumpulkan data melalui wawancara, observasi, dan dokumentasi dari pimpinan pesantren, pengurus, staf pengajar, dan santri. Analisis data dilakukan dengan model interaktif yang meliputi reduksi data, penyajian, dan penarikan kesimpulan. Temuan ini mengungkapkan bahwa kepemimpinan visioner dan inklusif memainkan peran penting dalam mendorong inovasi di pesantren, meski menghadapi hambatan internal terhadap perubahan. Pesantren yang mengelola proses perubahan secara efektif menunjukkan potensi untuk menjadi pusat inovasi dengan mengintegrasikan teknologi digital dengan pendidikan Islam tradisional. Pesantren-pesantren ini melestarikan nilai-nilai inti mereka sambil mengadopsi alat dan pendekatan baru untuk meningkatkan pembelajaran dan administrasi. Studi ini menyimpulkan bahwa pesantren dapat berkembang di era digital dengan mengelola transformasi budaya secara strategis, mendorong inovasi, dan tetap setia pada misi pendidikannya. Hasilnya menunjukkan bahwa pimpinan pesantren harus memprioritaskan fleksibilitas, kolaborasi, dan kemampuan beradaptasi untuk menciptakan lingkungan yang kondusif bagi inovasi dan transformasi digital. Kata Kunci: Transformasi Budaya Organisasi; Strategi Inovasi; Pesantren; Era Digital.